2021
DOI: 10.1088/1402-4896/ac2da4
|View full text |Cite
|
Sign up to set email alerts
|

Simulating favorable adsorption in lithium-ion batteries using a novel cellular-automaton-based method

Abstract: The advances in micro and nano-technologies have increased the demand to study surface effects such as adsorption using novel methods. Cellular automata, being a simple and to some extend intuitive method, seems a great candidate. Here, we have developed a simple adsorption model based on cellular automata to model 'favorable' adsorption isotherms. Using intuitive local rules based on the three common adsorption isotherms, i.e., Langmuir, Elovich, and Hill-Deboer isotherms, the model matched the predicted beha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…However, our effective model helps to clarify the relative contributions of Na on defect sites, and Na adsorbed to graphitic layers to the capacity. The comparison between simulation and Langmuir theory 53 of the 1st cycle is shown in Fig. 11.…”
Section: Approximating Reversible and Irreversible Capacitiesmentioning
confidence: 99%
“…However, our effective model helps to clarify the relative contributions of Na on defect sites, and Na adsorbed to graphitic layers to the capacity. The comparison between simulation and Langmuir theory 53 of the 1st cycle is shown in Fig. 11.…”
Section: Approximating Reversible and Irreversible Capacitiesmentioning
confidence: 99%
“…[41] These methods could offer a meaningful understanding of the system's interactions, leading to fewer trials and errors for experimental parametrizations. [42][43][44][45][46] Using molecular dynamics (MD) simulations combined with a mathematical interpretation of the outputs, Alizadeh Sahraei et al [47] investigated the effect of cross-linking density and the number of graphene layers on the thickness and interaction energy in the interphase. They showed that the crosslinking density and, more precisely, the presence of the crosslinking bonds in the interphase significantly affect the interphase thickness in epoxy nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…[ 41 ] These methods could offer a meaningful understanding of the system's interactions, leading to fewer trials and errors for experimental parametrizations. [ 42–46 ]…”
Section: Introductionmentioning
confidence: 99%